The essential Vedanta : a new source book of Advaita Vedanta - Deutsch, Eliot; Dalvi, Rohit (New Age Books, 2006)
Divided in 3 parts, this book deals with the background in tradition; and with philosophical and cultural background; and describes sources of "Advaita Vedanta" such as Gaudapada, Samkara, Suresvara, Mandana Mishra, and others.